PANCON- 9 Chitwan (Journal of Psychiatrists' Association of Nepal, 2022)
Collection of abstracts presented during the 9th National conference of Psychiatrists' Association of Nepal (PANCON) 2022 at Chitwan. Theme: Mental Health in a Changing World.